Edge Domination in Web Graph - Omran, A. A.; Al-Harere, M. N. (مجلة كلية التربية, 2021)
Let {\ \ γ}^e(G) be the edge domination number of a graph. A “web graph” W(s,t) is obtained from the Cartesian product of cycle graph of order s\ and path graph of order\ t. In this paper, edge domination number of the web graph is determined.Mathematical subject classification: 05C69
Keywords: Edge